The Relationship Between Entrepreneurial Orientation And Entrepreneurial Leadership Towards SME Performance : Mediating Factor Of Innovation Performance - Abdul Rahman, Nurulhasanah (2016)
Despite the extensive research in the domain of Entrepreneurial Orientation (EO) and Entrepreneurial Leadership (EL), very little work has been done on small and medium enterprises (SME). There is numerous financial assistance and supports have been provided to SME, however the SME Performance is still considered as low. By taking into account the relevance of these research topics, this study aims to identify the relationship between EO and EL towards SME Performance with Innovation Performance as a mediator. In order to achieve these objectives, quantitative approach is chosen and questionnaires are collected from 285 SME in Penang. The sampling technique used is Disproportionate Stratified Systematic Sampling.